2021
DOI: 10.5194/aab-64-83-2021
|View full text |Cite
|
Sign up to set email alerts
|

Determining the factors affecting the gestational length in sheep

Abstract: Abstract. This research aimed to determine the effects of body weight, the body condition score (BCS), body measurements, birth type (single offspring or twin birth), birth weight and sex on the gestational length in sheep (n=111). Karayaka sheep raised on a private farm were used in the study. Progeny yield characteristics in sheep were also determined (n=139). Estrus was monitored daily using teaser rams from August to September 2016. According to our findings, the pregnancy rate, infertility rate, fecundity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…This result supported by previous flushing study by using different kinds of fat at does 14 . The length of gestation in this study (141-144 days) shorter than data (148-151) reported by Celik et al 43 . The gestational length is affected by litter size, where higher litter size will have shorter gestational length compare to singlet one.…”
Section: Discussioncontrasting
confidence: 69%
“…This result supported by previous flushing study by using different kinds of fat at does 14 . The length of gestation in this study (141-144 days) shorter than data (148-151) reported by Celik et al 43 . The gestational length is affected by litter size, where higher litter size will have shorter gestational length compare to singlet one.…”
Section: Discussioncontrasting
confidence: 69%
“…Body measurements, such as thoracic circumference have been used in the definition of adult size, nutritional status, and physiological maturity in cattle (Rocha et al, 2003) and white-tailed deer (Uvalle- Sauceda et al, 2013), which allow the establishment of the relationship between body conformation and functionality and length of productive life of animals (Strapák et al, 2010). The thoracic circumference is related to body condition score (Tozlu Celik et al, 2021) and body weight (Worku, 2019;Chay-Canul et al, 2019) in sheep. Thus, apparently, in the present study greater thoracic circumference was linked with greater body energy reserves, and greater body fat of deer at about the middle of pregnancy predicted the number of fetuses they carry (Johnstone-Yellin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%